2018
DOI: 10.1002/ijop.12477
|View full text |Cite
|
Sign up to set email alerts
|

The model of children's social adjustment under the gender‐roles absence in single‐parent families

Abstract: This study aimed to evaluate the effects of the gender-role types and child-rearing gender-role attitude of the single-parents, as well as their children's gender role traits and family socio-economic status, on social adjustment. We recruited 458 pairs of single parents and their children aged 8-18 by purposive sampling. The research tools included the Family Socio-economic Status Questionnaire, Sex Role Scales, Parental Child-rearing Gender-role Attitude Scale and Social Adjustment Scale. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
(25 reference statements)
0
24
0
2
Order By: Relevance
“…However, it does not mean that single‐parent guardianship is the best type of guardianship. Previous studies have demonstrated that children in single‐parent custody have difficulties establishing gender roles, and children exhibit common psychological defects, such as poor speech, emotional apathy, violence, etc . For grandparent guardianship, the backward parenting style of grandparents maintains that satisfying children's material conditions is a good method of child rearing .…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not mean that single‐parent guardianship is the best type of guardianship. Previous studies have demonstrated that children in single‐parent custody have difficulties establishing gender roles, and children exhibit common psychological defects, such as poor speech, emotional apathy, violence, etc . For grandparent guardianship, the backward parenting style of grandparents maintains that satisfying children's material conditions is a good method of child rearing .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, girls in single-parent households exhibited only a slightly more feminine personality compared to their peers in nuclear families [15]. Still, in China, researchers found that factors such as income, educational level, and the single parent's own gender attitudes were better predictors of the formation of children's gender roles than just single parenthood alone [16]. Given the diversity of family structures worldwide, it is possible that these different structures may even positively shape adolescents' perceptions of masculinities and femininities [17e19].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, however, studies have appeared that note the positive functions of gender stereotypes associated with the translation of social experience and social adaptation of the individual (Chen et al, 2019;Piotrowski et al, 2019).…”
Section: Problem Statementmentioning
confidence: 99%